Field Evidence of Colonisation by Holm Oak, at the Northern Margin of Its Distribution Range, during the Anthropocene Period - Delzon, Sylvain; Urli, Morgane; Samalens, Jean-Charles; Lamy, Jean-Baptiste; Lischke, Heike; Sin, Fabrice; Zimmermann, Niklaus E.; Porte, Annabel J. (PLOS ONE, 2013)
A major unknown in the context of current climate change is the extent to which populations of slowly migrating species, such as trees, will track shifting climates. Niche modelling generally predicts substantial northward shifts of suitable habitats. There is therefore an urgent need for field-based forest observations to corroborate these extensive model simulations. We used forest inventory data providing presence/absence information from just over a century (1880-2010) for a Mediterranean species (Quercus ilex) in forests located at the northern edge of its distribution. The main goals of the study were (i) to investigate whether this species has actually spread into new areas during the Anthropocene period and (ii) to provide a direct estimation of tree migration rate. We show that Q. ilex has colonised substantial new areas over the last century. However, the maximum rate of colonisation by this species (22 to 57 m/year) was much slower than predicted by the models and necessary to follow changes in habitat suitability since 1880. Our results suggest that the rates of tree dispersion and establishment may also be too low to track shifts in bioclimatic envelopes in the future. The inclusion of contemporary, rather than historical, migration rates into models should improve our understanding of the response of species to climate change.
APSAPSThe following values have no corresponding Zotero field: pub-location: 1160 BATTERY STREET, STE 100, SAN FRANCISCO, CA 94111 USA publisher: PUBLIC LIBRARY SCIENCE
Keywords: mediterranean species; niche modelling; Quercus ilex